2009
DOI: 10.1007/bf03246156
|View full text |Cite
|
Sign up to set email alerts
|

Novel PVC-based coated graphite electrode for selective determination of quinoline yellow

Abstract: Novel coated graphite electrode (CGE) for the determination of quinoline yellow (QY), an artificial food colorant, was evaluated based on the use of tetraphenylphosponium-QY ion-pair complex as the electroactive substance. The electrode revealed linear emf-pQY response over wide concentration ranges (1.0 × 10 -1 ~ 5.0 × 10 -5 M ) with a slope -30.1 ± 0.2 mV decade -1 and a limit of detection of 4.0 × 10 -5 M. The electrode showed good stability, reproducibility and fast response (<5 s). It can be used in wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Electroanalytical technology also gained an important place in the detection of quinoline yellow due to its simplicity, high sensitivity and versatility. For instance, a coated graphite electrode was reported for the detection of quinoline yellow [8]. The linear range was 0.04-0.08 M, and the detection limit was 32.96 lM.…”
Section: Introductionmentioning
confidence: 99%
“…Electroanalytical technology also gained an important place in the detection of quinoline yellow due to its simplicity, high sensitivity and versatility. For instance, a coated graphite electrode was reported for the detection of quinoline yellow [8]. The linear range was 0.04-0.08 M, and the detection limit was 32.96 lM.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mercury electrode is toxic and can lead to environmental pollution. To overcome the disadvantages of mercury electrodes, nonmercury electrodes, such as a coated graphite electrode (Rouhani & Haji-ghasemi, 2009) and a carbon nanotubes-modified glassy carbon electrode (Zhao, Zhang, Wu, Chen, & Zhou, 2011), have been developed for the electrochemical determination of quinoline yellow. However, to the best of our knowledge, electrochemical detection of quinoline yellow using PVP-modified electrode is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1, the LOD of the modified electrode was compared with other reported previously (Cinti et al, 2014;Hosu et al, 2016;Piovesan and Spinelli, 2014;Rouhani and Haji-Ghasemi, 2009;Stevic et al, 2012). It can be suggested that the modified electrode in this work has better sensitivity.…”
Section: Effect Of Varying Quinoline Concentration and Limit Of Detecmentioning
confidence: 86%